Coupled extremely light Ca and Fe isotopes in peridotites. (1st July 2017) - Zhao, Xinmiao; Zhang, Zhaofeng; Huang, Shichun; Liu, Yufei; Li, Xin; Zhang, Hongfu
Abstract: Large metal stable isotopic variations have been observed in both extraterrestrial and terrestrial samples. For example, Ca exhibits large mass-dependent isotopic variation in terrestrial igneous rocks and mantle minerals (on the order of ∼2‰ variation in 44 Ca/ 40 Ca). A thorough assessment and understanding of such isotopic variations in peridotites provides important constraints on the evolution and compositon of the Earth's mantle. In order to better understand the Ca and Fe isotopic variations in terrestrial silicate rocks, we report Ca isotopic compositions in a set of peridotitic xenoliths from North China Craton (NCC), which have been studied for Fe isotopes. These NCC peridotites have large Ca and Fe isotopic variations, with δ 44/40 Ca ranging from −0.08 to 0.92 (delta value relative to SRM915a) and δ 57/54 Fe (delta value relative to IRMM-014) ranging from −0.61 to 0.16, and these isotopic variations are correlated with large Mg# (100 × Mg/(Mg + Fe) molar ratio) variation, ranging from 80 to 90. Importantly, NCC Fe-rich peridotites have the lowest 44 Ca/ 40 Ca and 57 Fe/ 54 Fe ratios in all terrestrial silicate rocks. In contrast, although ureilites, mantle rocks from a now broken differentiated asteroid(s), have large Mg# variation, from 70 to 92, they have very limited δ 57 Fe/ 54 Fe variation (0.03–0.21, delta value relative to IRMM-014). Our model calculations show that the coupled extremely light Ca-Fe isotopic signatures in NCC Fe-rich peridotites most likely reflect kinetic isotopic fractionation during melt-peridotite reaction on a timescale of several to 10 4 years. In addition, our new data and compiled literature data show a possible compositional effect on the inter-mineral Ca isotopic fractionation between co-existing clinopyroxene and orthopyroxene pairs.